Rhabdoid Tumour of Kidney with Metastasis to Ovary - A Rare Presentation - Chhanda Das; Madhumita Mukhopadhyay; Ashis Kumar Saha; Tamannya Parvin (JCDR Research and Publications Pvt. Ltd., 2016)
Rhabdoid tumour of kidney is a rare highly aggressive malignancy of early childhood. Here we are reporting an infant of six months who presented with mass abdomen in our hospital in the department of surgery. The computerized tomography finding was a hypoechoic mass occupying most of the kidney. Laparotomy followed by nephrectomy was performed. The ovary also found involved by a tumour mass, which also was excised On gross appearance the mass was solid, nodular, and variegated measuring 6 cm x 5.5 cm occupying most of the kidney. Histopathologically, it was diagnosed as rhabdoid tumour of the kidney, ovary also showed metastatic deposits from kidney mass. It was reported as rhabdoid tumour of kidney metastasizing to ovary. Immunohistochemistry was found positive for vimentin in both kidney and ovary section. As it is a very aggressive tumour early diagnosis is essential for the treatment and patient survival.